Effect of β-lactoglobulin on perception of astringency in red wine as measured by sequential profiling. (August 2020) - Olatujoye, Jumoke B.; Methven, Lisa; Jauregi, Paula
Abstract: Astringency is a predominant sensory attribute that influences the overall quality of red wine. The application of whey proteins as functional and nutritional food additives is popular but their use is uncommon to enology. Here whey proteins as a suitable food component to improve the sensory quality of red wine were investigated. This work focused on the sensory perception of astringency in red wine treated with β-lactoglobulin and gelatin. Ovalbumin precipitation method was used to assess astringency pre- and post-treatment and compared to the perceived astringency. A sequential profiling sensory technique was used to evaluate astringency in relation to other attributes over repeated consumption of red wine. The intensity of astringency increased insignificantly over repeated sips at 60 s intervals for the treated and untreated red wine. The difference in astringency perception (p < 0.05) between the wine samples was shown at 30 s after swallowing. Wines treated with β-lactoglobulin and gelatin significantly reduced astringency and the total polyphenol content. The reduction in astringency indicates that these proteins actively bind and precipitate polyphenols which are known to contribute to perception of astringency. Furthermore, the good agreement between the chemical and sensory methods supports this mechanism for reduction of astringency. Highlights: Higher intensity of astringency perceived in the control than in β-lactoglobulin and gelatin treated wines. Other attributes of the red wine were insignificantly modulated by β-lactoglobulin. Analytical determination of astringency agreed with perceived astringency. Reduction of astringency by β-lactoglobulin wine is based on the principle of protein precipitation.